2021
DOI: 10.1161/circresaha.120.317219
|View full text |Cite|
|
Sign up to set email alerts
|

Different DOACs Control Inflammation in Cardiac Ischemia-Reperfusion Differently

Abstract: Rationale: While thrombin is the key protease in thrombus formation, other coagulation proteases, such as fXa or activated protein C (aPC), independently modulate intracellular signaling via partially distinct receptors. Objective: To study the differential effects of fXa or fIIa inhibition on gene expression and inflammation in myocardial ischemia-reperfusion injury (IRI). Methods and Results: Mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
2
22
1
Order By: Relevance
“…Six DEGs (ARG1, CLEC4E, SAMSN1, FKBP5, NAMPTL, and S100A12) were obtained, all of which indicated great performance in identifying patients with STEMI from SCAD with AUC > 0.9 (Figure 3a). However, we noticed differences in our research compared with the previous study, which observed five differentially expressed genes FKBP5, S100P, SAMSN1, CLEC4E, and S100A12 [17][18][19][20][21][22][23][24][25][26]; we observed two additional novel DEGs ARG1 and NAMPTL; different expression of S100P among STEMI and SCAD was failed to be observed in our study. This variety was caused by various preprocessing of the expression data: in our analysis, before DEGs analysis, we performed clustering with gene expression to identify experimentally caused outliers and discarded five samples including three patients with STEMI and 2 with SCAD (Figure 1a).…”
Section: Discussioncontrasting
confidence: 99%
“…Six DEGs (ARG1, CLEC4E, SAMSN1, FKBP5, NAMPTL, and S100A12) were obtained, all of which indicated great performance in identifying patients with STEMI from SCAD with AUC > 0.9 (Figure 3a). However, we noticed differences in our research compared with the previous study, which observed five differentially expressed genes FKBP5, S100P, SAMSN1, CLEC4E, and S100A12 [17][18][19][20][21][22][23][24][25][26]; we observed two additional novel DEGs ARG1 and NAMPTL; different expression of S100P among STEMI and SCAD was failed to be observed in our study. This variety was caused by various preprocessing of the expression data: in our analysis, before DEGs analysis, we performed clustering with gene expression to identify experimentally caused outliers and discarded five samples including three patients with STEMI and 2 with SCAD (Figure 1a).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, in addition to its effect on p21, aPC reverses glucoseinduced expression of p66 Shc , a mitochondrial protein promoting ROS-generation, in podocytes (glomerular cells) and macrophages (9,11). Furthermore, inhibitors of coagulation factors fIIa (dabigatran) or fXa (rivaroxaban) differentially regulate aPC generation, which is linked to differential gene expression and epigenetic marks (55). Epigenetic control of gene-expression by aPC provides a rational for the long-lasting effects of therapeutic aPC applications despite its short half-life (56) andconsidering the broad cytoprotective effects of aPC -may be relevant in other disease settings (34,57).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent follow-up studies, we have investigated the transcriptomic profile of aPC treatment in murine myocardial IRI in comparison to direct oral anticoagulants FXa inhibitor (FXai, rivaroxaban) and FIIa inhibitor (FIIai, dabigatran). In this regard, the dosing regimens for both anticoagulants were experimentally determined to provide comparable anticoagulant effects and the infarct sizes ( 84 ). The results from our study show that the gene expression profile of aPC-treated mice resembled that of mice treated with FXa inhibitor (FXai, rivaroxaban) ( 84 ).…”
Section: Activated Protein C and Thrombo-inflammation In Cardiovascul...mentioning
confidence: 99%
“…In this regard, the dosing regimens for both anticoagulants were experimentally determined to provide comparable anticoagulant effects and the infarct sizes ( 84 ). The results from our study show that the gene expression profile of aPC-treated mice resembled that of mice treated with FXa inhibitor (FXai, rivaroxaban) ( 84 ). On the contrary, mice treated with FIIa inhibitor (FIIai, dabigatran) had a markedly different gene expression profile compared to FXai or aPC treated mice.…”
Section: Activated Protein C and Thrombo-inflammation In Cardiovascul...mentioning
confidence: 99%